2022
DOI: 10.1111/jnc.15679
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 infection impacts carbon metabolism and depends on glutamine for replication in Syrian hamster astrocytes

Abstract: COVID‐19 causes more than million deaths worldwide. Although much is understood about the immunopathogenesis of the lung disease, a lot remains to be known on the neurological impact of COVID‐19. Here we evaluated immunometabolic changes using astrocytes in vitro and dissected brain areas of SARS‐CoV‐2 infected Syrian hamsters. We show that SARS‐CoV‐2 alters proteins of carbon metabolism, glycolysis, and synaptic transmission, many of which are altered in neurological diseases. Real‐time… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 84 publications
2
16
0
Order By: Relevance
“…Abnormal astrocyte function impairs neuronal survival and promotes neurodegeneration ( 22 , 23 ). Astrocytes from both hamsters and brain organoids have been shown to be susceptible to SARS-CoV-2 infection ( 15 , 24 , 25 ). Given the essential role of astrocytes in neuronal health and synapse function, it is possible that the neurological symptoms of COVID-19 result in part from the direct infection of astrocytes by SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal astrocyte function impairs neuronal survival and promotes neurodegeneration ( 22 , 23 ). Astrocytes from both hamsters and brain organoids have been shown to be susceptible to SARS-CoV-2 infection ( 15 , 24 , 25 ). Given the essential role of astrocytes in neuronal health and synapse function, it is possible that the neurological symptoms of COVID-19 result in part from the direct infection of astrocytes by SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear now that different viruses, e.g., influenza virus, can infect the CNS and cause neurological disorders [ 149 ]. However, with the current COVID-19 pandemic, much more attention has been given to viruses that are known to be non-neurotropic, that is, their primary site of infection is not the brain, but yet are “neuropathogenic”, which may lead to neurological abnormalities and psychiatric disorders [ 148 , 150 , 151 , 152 ]. Interestingly, some speculations about some kind of viral etiology behind neurological disorders such as Parkinson’s disease, acute disseminated encephalomyelitis, and multiple sclerosis have gained attention as coronaviruses, such as HCoV-229E and HCoV-OC43, have been detected in patients’ brains [ 153 , 154 ].…”
Section: Innate Immune Response: the Front Line In The Fight Against ...mentioning
confidence: 99%
“…It is worth mentioning that wild type mice are not permissive to SARS-CoV-2 infection due to structural differences on ACE-2, although the use of the Variant of Concern (VOC) Delta B1.617.2 (Yang et al 2023 ), or a mouse adapted strain (MA10) (Amruta et al 2022 ) had indicated otherwise. For this reason, most in vitro studies used primary cells either from K18-ACE-2 transgenic mice, hamsters (Rothan et al 2022 ; de Oliveira et al 2022 ) or wild-type animals pre-treated with an adenovirus (AAV-hACE-2) as a vector to induce the expression of hACE-2 (Song et al 2021b ; Monje and Iwasaki 2022 ). Other studies also used human-derived induced-pluripotent stem cells (iPSCs) as well as brain organoids (Ramani et al 2020 , 2021 ; Jacob et al 2020 ; Song et al 2021b ; Samudyata et al 2022 ; Kong et al 2022 ), which are useful tools for the study of many aspects of brain development, function, metabolism and has already been used for the studies of other viral infection, including ZIKA virus (Cugola et al 2016 ), dengue virus, influenza virus and also SARS-CoV-2, as reviewed (Harschnitz and Studer 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many different animal models were established to investigate the biology of SARS-CoV-2 in vivo; from zebrafish (Ventura Fernandes et al 2022 ; Kraus et al 2022 ), mice (Kumari et al 2021 ; Rhea et al 2021 ) and hamsters (Rosenke et al 2020 ; Zazhytska et al 2022 ; de Oliveira et al 2022 ) to ferrets (Kim et al 2022 ) and macaques (Rutkai et al 2022 ; Beckman et al 2022 ), as reviewed (Muñoz-Fontela et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation